2020
DOI: 10.1016/j.erss.2020.101448
|View full text |Cite
|
Sign up to set email alerts
|

Do passive houses need passive people? Evaluating the active occupancy of Passivhaus homes in the United Kingdom

Abstract: The Passivhaus model emphasises a high standard of building fabric insulation and controlled ventilation with heat recovery in order to achieve comfort and reduce energy use. The implication is that environmental control is achieved by the building fabric and ventilation system with little need for significant occupant interaction or behaviour change in order to achieve comfort and energy efficiency. This paper challenges such views with new research that draws upon empirical data from case studies of houses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This study found that passive solutions or solutions where households have to engage actively, like flipping a switch, are more effective than relying on information or feedback as a source for encouraging behavioral changes, which has also been found elsewhere [6,9,10]. This implies that when constructing new residential buildings where active engagement of households is encouraged, solutions to engage households physically-to make them do something-should be a solution.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This study found that passive solutions or solutions where households have to engage actively, like flipping a switch, are more effective than relying on information or feedback as a source for encouraging behavioral changes, which has also been found elsewhere [6,9,10]. This implies that when constructing new residential buildings where active engagement of households is encouraged, solutions to engage households physically-to make them do something-should be a solution.…”
Section: Discussionsupporting
confidence: 59%
“…Some studies suggest that households need to interact with all the buildings' energyreducing features in order to get the best performance [9], while others indicate that the interaction with the smart features of a home environment is short-lived [10]. In this study, it was found that households were initially interested in engaging actively with all the smart features that Greenhouse promised, but that this window of opportunity was missed because of malfunctions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is relevant to Active Homes, which have the potential to change residents' relationships to energy through the inclusion of energy-generation technologies such as solar photovoltaics (PV), which may require active administration (Hansen & Hauge 2017). Existing research into low carbon housing has highlighted potential tensions between expert expectations of residents and the experiences of residents themselves (Zhao & Carter 2020;Cherry et al 2017). However, previous research into 'prosuming' households has largely focused on those who have chosen to install few or individual technologies, reflecting a sample who are energy-minded and engaged (Stikvoort et al 2020).…”
Section: Expert Visions Of Residentsmentioning
confidence: 99%
“…Concurrently, the thermal transmittance values of an enclosure are regulated in Chile while taking into consideration its climatic and performance similarities with other European countries, such as the United Kingdom or Spain. Additionally, when considering levels of hermeticity, establishing a limit on the energy demand may still be insufficient [13][14][15][16][17], as is the case in countries such as Sweden and Portugal, where the imposition of regulations on the transmittance levels of the envelope-as in the previous examples-failed to substantially reduce the energy demand of the dwellings [12,18]. As a policy to mitigate these gaps, the European Union, through its Directive 2010/31/EU, stipulates that from the year 2021, houses should be built with near-zero energy consumption restrictions in place [19].…”
Section: Introductionmentioning
confidence: 99%